PENGARUH SISTEM KOMPUTERISASI TERHADAP TINGKAT KEPUASAN PELAYANAN MASYARAKAT DI LINGKUNGAN KECAMATAN SIBOLGA SELATAN. - Panggabean, Nanda Pratama; Mhd. Shafwan Koto; Safran Matondang; Amaludin Sikumbang; Delita Sihotang (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
The rapid development of information technology has created a new revolution: the shift from conventional work systems to the digital era. Within government agencies, this change is marked by the abandonment of traditional government systems, synonymous with analog and paper-based administration, and a shift toward electronic government (e-government), which utilizes information technology to improve relations between the government and other parties. Based on the research results, it shows that the relationship between computerized systems and public service satisfaction is a strong relationship.